Price theory and applications - Landsburg, Steven E. 1954- (Singapore World Scientific, 2024)
Price Theory and Applications challenges students to master the economic way of understanding the world, with equal emphasis on intuition and precise logic, and special emphasis on the interplay between them. The writing is inviting, humorous, and sometimes folksy, without sacrificing the insistence that arguments need to be airtight. Important concepts are introduced via entertaining examples and fleshed out with rigor. The learning experience is supported by a vast number of intriguing and entertaining exhibits, examples, numerical exercises, and problem sets, some integrated within the text and others included at the end of chapters. The problems vary widely in their demands on students - some are straightforward applications of the theory, while others require a great deal of creativity and a willingness to think considerably outside the box"--
Contents: Chapter 1 - Supply, Demand, and Equilibrium - - Chapter 2 - Prices, Costs, and the Gains from Trade - - Chapter 3 - The Behavior of Consumers - - Chapter 4 - Consumers in the Marketplace - - Chapter 5 - The Behavior of Firms - - Chapter 6 - Production and Costs - - Chapter 7 - Competition - - Chapter 8 - Welfare Economics and the Gains from Trade - - Chapter 9 - Knowledge and Information - - Chapter 10 - Monopoly - - Chapter 11 - Market Power, Collusion, and Oligopoly - - Chapter 12 - The Theory of Games - - Chapter 13 - External Costs and Benefits - - Chapter 14 - Common Property and Public Goods - - Chapter 15 - The Demand for Factors of Production - - Chapter 16 - The Market for Labor - - Chapter 17 - Allocating Goods Over Time - - Chapter 18 - Risk and Uncertainty - - Chapter 19 - What is Economics?.
Includes bibliographical references and index.
Keywords: Microeconomics; Prices